Predication of labour forces and personal expenditures development in Czech food industry branches in the Czech Republic till 2013 - M. Putićová; P. Froněk; J. Mezera (Agricultural Economics (AGRICECON), 2007)
Production of food and beverages is one of the Czech traditional branches of processing industry. The article tries to describe the model prediction on the sector structure development oriented on labour and personal costs in food industry sector up to 2013 and it is based on the continuous monitoring of these indicators in the period 2000-2005. Except regress analysis of time orders, there was used the method of exponential smoothing. With regard to certain antagonistic tendencies, i.e. the lasting fall of the number of workers in the monitored period but at the same time the growth of personal costs, there were projected separate predictions of these indicators up to 2013, aimed namely at the set of companies with 20 and more employees. The prediction of the selected data up to the year 2013 is based on the running results of the Research Plan of the Research Institute of Agricultural Economics (VÚZE). The probable development of the number of workers and personal costs in the individual branches of food industry is characterised.